Comparison of fluticasone propionate with beclomethasone dipropionate in moderate to severe asthma treated for one year. International Study Group. Issue 8 (August 1993) - Fabbri, L; Burge, P S; Croonenborgh, L; Warlies, F; Weeke, B; Ciaccia, A; Parker, C
Abstract : BACKGROUND--High dose inhaled glucocorticosteroids are increasingly used in the management of patients with moderate to severe asthma. Although effective, they may cause systemic side effects. Fluticasone propionate is a topically active inhaled glucocorticosteroid which has few systemic effects at high doses. METHODS--Fluticasone propionate, 1.5 mg per day, was compared with beclomethasone dipropionate at the same dose for one year in patients with symptomatic moderate to severe asthma; 142 patients received fluticasone propionate and 132 received beclomethasone dipropionate. The study was multicentre, double blind and of a parallel design. For the first three months patients attended the clinic every four weeks and completed daily diary cards. For the next nine months they were only seen at three monthly intervals in the clinic. RESULTS--During the first three months diary card peak expiratory flow (PEF) rate and lung function measurements in the clinic showed significantly greater improvement in patients receiving fluticasone propionate (difference in morning PEF 15 l/min (95% CI 6 to 25)), and these differences were apparent at the end of the first week. The improved lung function was maintained throughout the 12 month period and the number of severe exacerbations in patients receiving fluticasone propionate was reduced by 8% compared with those receiving beclomethasone dipropionate. No significant differences between the two groups were observed in morning plasma cortisol levels, urinary free cortisol levels, or response to synthetic ACTH stimulation. In addition, both the rates of withdrawal and of adverse events were low, and there were fewer exacerbations of asthma with fluticasone propionate than beclomethasone dipropionate. CONCLUSIONS--This study shows that fluticasone propionate in a daily dose of 1.5 mg results in a significantly greater increase in PEF and asthma control than the same dose of beclomethasone dipropionate, with no increase in systemic or other side effects.